Analisis Strategi Manajemen Operasional Untuk Pendidikan - Riangga Fathurrahman (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
The quality of education is one of the important issues that draws attention in various educational discussions in Indonesia. In educational organizations, as in any other organization, achieving good and effective organizational performance becomes the focus of education managers. The impacts of globalization, the development of science and technology, and modern learning models and methods are all contributing factors. This research refers to literature research. To obtain research data, the researcher collects, analyzes, and compiles sources from articles, books, and previous research papers on the application of strategic management in education. The researcher then supplements the strategic management data to improve the quality of education. Teachers and economic policy researchers have started meeting to discuss policy changes in management and how to respond to them. To achieve superior organizational performance, an organization must be able to compete in both human resources and finances. Both are crucial elements for an organization. The role of leadership is a key element in achieving this goal. Improving the quality of education in educational institutions, addressing global challenges, enhancing the quality of educational management, improving the quality of the learning process, improving the quality of human resources in education, as well as strategic management and operational management in building network management.